Disasters and Nurses' Preparedness for Disasters in Turkey: Literature Review - Gülcan Taşkıran; Ülkü Baykal (Association of Nurse Managers, 2017)
Since disasters often strike without warning, healthcare providers, especially nurses must be prepared with appropriate competencies for disaster procedures. Nurses' preparedness for disasters need to be evaluated to aid in the creation of effective national plans and educational programs. The purpose of the study is to present the current situation and to provide a working perspective on nurses' preparedness for disasters. It has been determined that studies that examine nurses' preparedness for disasters in Turkey are mostly descriptive and their samples are limited. It was seen that the studies in Turkey were carried out after 2010 and there was no research on this subject before. Studies have shown that nurses' basic competencies for disaster preparedness need to be developed, they need training programs and are willing to participate. The study revealed that the training of nurses for disasters in Turkey is inadequate and the nurses do not see themselves prepared and sufficient to intervene in disasters. When compared to other countries, it is seen that the studies done on this subject in Turkey are very few and it is necessary to carry out further research on the subject.